JURIDICAL ISSUES IN EMPLOYMENT TERMINATION DUE TO FORCE MAJEURE - Subagiyo, Dwi Tatak; Widjangkoro, Hanung (Faculty of Law, Universitas Lampung, 2024)
Termination of Employment Relations (PHK) represents a highly distressing event for workers, as it disrupts their livelihoods and results in significant economic challenges. Layoffs can lead to various conflicts and difficulties, underscoring the need for protective regulations that safeguard workers' rights. In the context of employment disputes related to force majeure, the COVID-19 pandemic fits within the force majeure category due to its unforeseen and uncontrollable nature, which impedes the company's ability to fulfill its contractual obligations. Judicial decisions, such as Case Number 30/Pdt.Sus-PHI/2020/PN Gresik, demonstrate how courts can fairly adjudicate employment cases by applying principles of force majeure, thus providing a balanced approach to resolving disputes arising from such unprecedented circumstances.